Changes in anti-fat weight bias in women after exposure to thin and plus-sized models. Issue 2 (1st June 2018) - Smirles, Kimberly Eretzian; Lin, Linda
Abstract: We examined whether exposing women to female models with different body sizes lead to changes in weight-based attitudes and whether evaluation focus altered the effects. Female college students (N = 214) were exposed to 22 images of either thin or overweight models. Participants rated models on either appearance or non-appearance characteristics and completed measures of anti-fat attitudes, thin ideal internalization, and demographics. Participants rated thin and overweight models equally attractive and sexy. Viewing overweight models showed a significant reduction in anti-fat attitudes. There were no effects for thin models or evaluation ratings. Discussion focuses on the implications of positive images of overweight individuals on social attitudes.